Positive and Negative Affect Schedule (Panas): Psychometric Properties and Discriminative Capacity in Several Chilean Samples - Vera-Villarroel, P; Celis-Atenas, K; Contreras-Ramirez, D; Lillo-Vidal, S (SAGE Publications Inc., 2019)
We evaluated the factor structure, reliability, and discriminative capacity of the Positive and Negative Affect Schedule (PANAS) questionnaire in four different samples: two general adult populations (N = 1,548, N = 964), one adolescent population (N = 1,044), and young people with depressive symptomatology (N = 307). Exploratory factor analyses (EFAs) were performed with subsamples from Studies 1 (n = 773) and 2 (n = 527), finding that the two- and three-factor solutions had a good fit. In a confirmatory factor analysis, the two-factor solution resulted in an adequate fit in a second set of subsamples from both studies (n = 775, n = 517). In Study 3, we found good convergent and divergent validity with adequate and significant correlations found for depression (Beck’s Depression Inventory), anxiety (State–Trait Anxiety Inventory), and neuroticism and extroversion (Big Five Inventory). In Study 4, the results of an EFA performed in a subsample (n = 154) found that the two- and three-factor solutions were appropriate with the former solution being confirmed in a second subsample (n = 153). Reliability was α =.85 for positive affect and α =.87 for negative affect. The PANAS questionnaire showed adequate indicators of validity and reliability in adult and adolescent populations as well as in a sample with depressive symptoms. © The Author(s) 2017.